Hubungan Antara Kesediaan Terhadap Pelaksanaan Kurikulum Tingkat Satuan Pendidikan Dengan Tekanan Kerja Pada Guru Mata Pelajaran Ekonomi - Lisa Agustina; Nur Aishah Buang; Muhammad Hussin (Jurnal Pencerahan, 2017)
This study aims to identify the relationship between willingness and pressure amongst teacher of Economics in implementing kurikulum tingkat satuan pendidikan. This study used a questionnaire with 109 teachers from twelve middle schools in Aceh Besar district, who were directly involved in the process of implementing the curriculum. Descriptive analyses used were frequency, percent, mean value and standard deviation. It was found that the level of willingness of the teachers was at a moderate level with an overall mean value of 3.46. Meanwhile, the level of pressure was at a high level with an overall mean value at 3.56. An inferential statistical correlation test was used to test hypotheses. It was found that there was a relationship between the level of willingness and the level of pressure. It can be concluded that willingness will influence the pressure of the teachers to implement the curriculum.